Biosensors Micro and Nanoscale Applications - Rinken, Toonika (IntechOpen, 2015)
Nowadays, the implementation of novel technological platforms in biosensor-based developments is primarily directed to the miniaturization of analytical systems and lowering the limits of detection. Rapid scientific and technological progress enables the application of biosensors for the online detection of minute concentrations of different chemical compounds in a wide selection of matrixes and monitoring extremely low levels of biomarkers even in living organisms and individual cells. This book, including 16 chapters, characterizes the present state of the art and prospective options for micro and nanoscale activities in biosensors construction and applications.